Multi hierarchical construction-induced superior capacitive performances of flexible electrodes for wearable energy storage. (April 2017) - Dong, Liubing; Liang, Gemeng; Xu, Chengjun; Liu, Wenbao; Pan, Zheng-Ze; Zhou, Enlou; Kang, Feiyu; Yang, Quan-Hong
Abstract: A multi hierarchical construction is designed for flexible supercapacitor electrodes. Specifically, we chose activated carbon fiber cloth (ACFC) as flexible substrates, deposited polyaniline (PANI) on fiber surface first, then constructed continuous carbon nanotube (CNT) networks between fibers and finally deposited PANI on the CNT networks to obtain ACFC/PANI/CNT/PANI textile electrodes. Repeated deposition of PANI and application of ACFC substrate lead to high content of electrochemically active materials ( i.e., PANI and activated carbon fiber); meanwhile, these active materials are located in different locations in the electrodes (fiber itself, fiber surface and the space between fibers), thus avoiding serious aggregation. The fabricated electrodes exhibit superior capacitive performances: areal capacitance, energy density and power density are 4039 mF cm −2, 131 μW h cm −2 and 11424 μW cm −2, respectively, remarkably higher than those of previously reported flexible supercapacitor electrodes; our electrodes also have good cycling stability and flexibility. Furthermore, high-performance thick electrodes (capacitance: 7804 mF cm −2 ; energy output: 214 μW h cm −2 ) and flexible fiber-like electrodes (capacitance: 805 mF cm −2 ; energy density: 23 μW h cm −2 ) are easily produced from our textile electrodes. This study offers a new direction for optimizing micro-structures and electrochemical properties of flexible electrodes in wearable energy storage devices. Graphical abstract: Highlights: A multi hierarchical construction is designed for flexible supercapacitor electrodes. Uniform distribution of active materials with high loading in flexible electrodes is realized. Energy-storage ability of flexible supercapacitor electrodes is significantly enhanced.